1999
DOI: 10.1021/jm9900570
|View full text |Cite
|
Sign up to set email alerts
|

Paullones, a Series of Cyclin-Dependent Kinase Inhibitors:  Synthesis, Evaluation of CDK1/Cyclin B Inhibition, and in Vitro Antitumor Activity

Abstract: The paullones represent a novel class of small molecule cyclin-dependent kinase (CDK) inhibitors. To investigate structure-activity relationships and to develop paullones with antitumor activity, derivatives of the lead structure kenpaullone (9-bromo-7,12-dihydroindolo[3,2-d][1]benzazepin-6(5H)-one, 4a) were synthesized. Paullones with different substituents in the 2-, 3-, 4-, 9-, and 11-positions were prepared by a Fischer indole reaction starting from 1H-[1]benzazepine-2,5(3H,4H)-diones 5. Selective substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
226
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 309 publications
(232 citation statements)
references
References 40 publications
(92 reference statements)
3
226
1
2
Order By: Relevance
“…Paullones were initially identified as CDK inhibitors (11,12). However, during extensive selectivity studies, we found that paullones were also excellent inhibitors of GSK-3 (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paullones were initially identified as CDK inhibitors (11,12). However, during extensive selectivity studies, we found that paullones were also excellent inhibitors of GSK-3 (13).…”
Section: Discussionmentioning
confidence: 99%
“…Other paullones were synthesized as described previously (11). The synthesis and characterization of gwennpaullone (2-(4-aminobutoxy)-9-bromo-7,12-dihydroindolo [3,2-d](1)benzazepin-6(5H)-one hydrochloride or C-2-paullone) is outlined below.…”
Section: Synthesis and Immobilization Of Paullonesmentioning
confidence: 99%
See 1 more Smart Citation
“…7). The recently described paullones (57,58) were also found to be excellent GSK-3␤ inhibitors. 2 Another recently described CDK inhibitor derived from marine sponges, hymenialdisine, is equally efficient on GSK-3␤ and CDKs (59).…”
Section: Indirubins Inhibit In Vitro and In Vivo Tau Phosphorylation mentioning
confidence: 96%
“…Previous reports have found that, although lithium has no effect on PKA activity (72), indirubin-3-monoxime has a 300-fold greater effect on GSK-3 than PKA (73), and alsterpaullone has an undetermined effect on PKA. Interestingly, however, both indirubin-3-monoxime and alsterpaullone are also able to inhibit cyclin-dependent kinases (73,74). Therefore, as a negative control we also tested the cyclin-dependent kinase inhibitor roscovitine, which has no effect on PKA activity and has a 1000-fold greater effect on cyclin-dependent kinases than GSK-3 (71, 75), and found that it was unable to significantly block this PKA effect.…”
Section: Pka and Gsk-3 Synergize To Completely Block Ionomycininducedmentioning
confidence: 99%